Parameters for the evaluation of egg quality: a systematic review - Silva Neto, Pedro Abreu da; Costa, Beatriz Lopes da; Oliveira, Magnólia Carneiro de; Chaves, Maria Juciene Lima; Mendes, Luana Guabiraba; Monte, Antônia Lucivânia de Sousa (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2024)
Eggs have economic and nutritional potential, being a source of animal protein and are widely consumed in meals. Due to their importance, the objective of this paper is to compile, through a systematic review, information on parameters in egg quality. The search was conducted through Scientific Electronic Library Online (SCIELO), CAPES Periodic, ScienceDirect, and Google Scholar using the following terms: “Quality parameters of eggs” and “physicochemical parameters of eggs”. Eighteen studies were selected; out of the total, 33% of the contributions were from Brazil. Approximately 5 studies investigated age, bird genotypes, different forms of rearing and the influence of these factors on the quality of the eggs produced. Six papers sought to observe the effects of bird feeding on egg quality, while 3 works addressed the use of alternative methods for egg quality analysis. Two studies applied physical evaluations and microbiological analyses to verify the quality of commercialized eggs, and 2 studies presented different approaches involving physical or physicochemical methods for microbial control of eggs. It was concluded that egg quality can be determined by various parameters, whether with traditional methods or the application of alternative and innovative methodologies.